2019
DOI: 10.3389/fpsyg.2019.01239
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Facial Stimulation Implicitly Improves Evaluations of the Goodness of Attractive Others

Abstract: It has been well demonstrated that shared multisensory experiences between the self and others can influence the social perception of out-group members. Previous research has shown that the illusion of ownership over a dark-skinned rubber hand or full virtual body generated less negative implicit bias against people with dark skin. However, less is known about how perceived attractiveness difference between self and other affects social perception toward those others after shared multisensory experience. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Indeed, synchrony had the opposite effect on stereotyping than asynchrony by showing a significant reduction of the strength of the stereotype as assessed by the IAT. This finding is also consistent with previous studies showing that identifying with others can affect one's social perception (Mazzurega et al, 2011;Paladino et al, 2010) and, more importantly, implicit attitudes towards others (Jeong et al, 2019;Maister et al, 2013;Peck et al, 2013). More generally speaking, our findings are also consistent with the idea that synchronizing with the behavior of another person does not only tend to diminish self-other discrimination, but also to invite a kind of "feature migration" (Ma et al, 2019), so that features actually "belonging" to the other (such as race and other physical attributes or affective states: Ma et al, 2016;Ma et al, 2019) can become attached to one's selfrepresentation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, synchrony had the opposite effect on stereotyping than asynchrony by showing a significant reduction of the strength of the stereotype as assessed by the IAT. This finding is also consistent with previous studies showing that identifying with others can affect one's social perception (Mazzurega et al, 2011;Paladino et al, 2010) and, more importantly, implicit attitudes towards others (Jeong et al, 2019;Maister et al, 2013;Peck et al, 2013). More generally speaking, our findings are also consistent with the idea that synchronizing with the behavior of another person does not only tend to diminish self-other discrimination, but also to invite a kind of "feature migration" (Ma et al, 2019), so that features actually "belonging" to the other (such as race and other physical attributes or affective states: Ma et al, 2016;Ma et al, 2019) can become attached to one's selfrepresentation.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the correlations showed a tighter relationship between the IAT d score changes and agency than between the IAT and the ownership ratings, even though agency and ownership were strongly correlated. This is to some extent consistent with findings of our previous study (Ma et al, 2016), in which only agency ratings correlated with changes in selfother integration and mood, and with the observation that synchrony, but not ownership ratings, positively predict the implicit attitude towards others assessed by means of IAT (Jeong et al, 2019). These patterns suggest that agency and ownership ratings rely on overlapping but not completely identical informational resources, and that the relationship between agency and gender stereotype relies on information that is not shared with ownership.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may be relevant given that our hypothesis was that enfacing an unfamiliar other would induce children to generalize positive self-associations to others. Nevertheless, previous adult studies using multisensory illusion that did not include measures of “affect” (e.g., perceived likeness/similarity of the embodied other) have been successful in demonstrating the effect of blurring self-other boundaries on social processes (e.g., Maister et al, 2013b ; Jeong et al, 2019 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generalization of positive self-association induced by multisensory bodily illusions has been shown to extend beyond body-related aspects to the conceptual domain, whereby identifying with others affects attitudes toward other people ( Maister et al, 2013a ; Peck et al, 2013 ; Jeong et al, 2019 ). Relatedly, Salvato et al (2020) showed that participants exposed to images of larger bodies are more likely to implicitly associate the concept of “self” with “thin,” suggesting that comparisons between self- and other-representations may modulate body image ( Salvato et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%